PENINGKATAN KETERAMPILAN MENULIS TEKS BERITA DENGAN MENGGUNAKAN MODEL EXAMPLES NON EXAMPLES: DOI: https://doi.org/10.37850/cendekia.v12i1.80 - Suwarno (CENDEKIA, 2020)
This research report is motivated by 1) The process of learning Indonesian, especially aspects of writing skills in Class VIII A, SMP Negeri 1 Sekaran is still not satisfactory enough. The average score on the aspect of writing is still below the standard set at the beginning of the semester. 2) This requires the teacher to do remidial, however, sometimes the implementation of remedial is only a formality. Remedial is not done properly. Remedial is only done as a process of raising a child's value from a condition under minimal completeness to a condition of achieving minimal completeness. Research reports on learning to write news texts using the cooperative learning model Examples Non Examples through group assignments and individual assignments, researchers have done for up to two cycles. In each cycle there are four phases, namely (1) planning BP, (2) carrying out BP, (3) carrying out observations, and (4) making reflections. The four phases are planned and implemented to improve students' ability to write news texts through group assignments, and individual assignments using the Examples Non Examples model. The phases in the first cycle are designed as a result of reflection on daily learning activities. While the phases in the second cycle are designed from the results of the reflection of the first cycle, in this way it is expected that in the second cycle all students improve their ability to write news text with the Examples Non Examples model. From the results of the analysis of each cycle, it can be seen student learning outcomes have increased. In the pre-mastery stage students only scored 61% or enough categories, then in the first cycle the completeness value obtained by 72% was still sufficient category, at this stage increased by 11%. Then in cycle II the value of students' mastery learning increased even better than the first cycle, which is 89% and is included in the excellent category. In other words an increase of 27%, the 85% complete limit has been exceeded.